Effects of Methanol Leaf and Root Extracts of Lophira lanceolata on Haematological Indices and Tissue Histology in Bitis arietans Venom-Induced Toxicity in Wistar Rats - Emmanuel Askeb-nde Joel; Isaac John Umaru; Kyugah Jacob Tersur; Sukyakma Manu (African Journal of Biochemistry and Molecular Biology Research, 2026)
Snakebite envenomation frequently causes severe haematological disturbances through venom-induced haemotoxicity and systemic inflammatory responses. This study investigated the restorative effects of methanol leaf and root extracts of Lophira lanceolata on haematological indices in Bitis arietans venom-intoxicated Wistar rats. Thirty-six male rats were assigned to six groups: normal control, venom control, venom plus antiserum, venom plus leaf extract (200 mg/kg), venom plus root extract (200 mg/kg), and venom plus combined extracts. After 14 days of treatment, blood samples were analyzed for white blood cells, red blood cells, haemoglobin, platelets, and haematocrit. Venom intoxication induced significant leukocytosis, anaemia, thrombocytopenia, and reduced haematocrit, whereas treatment with L. lanceolata extracts, particularly the root extract, significantly improved these parameters toward normal levels. The root extract restored white blood cells to 8.40 ± 0.38 × 10⁹/L, red blood cells to 7.65 ± 0.30 × 10¹²/L, haemoglobin to 6.80 ± 0.20 g/dL, platelets to 425.50 ± 19.26 × 10⁹/L, and haematocrit to 20.50 ± 1.13%, indicating superior haematoprotective and anti-inflammatory effects relative to the leaf extract. Histological examination further confirmed these findings, showing that the extracts, especially the root, ameliorated venom-induced necrosis, hemorrhage, and congestion in liver and kidney tissues. These findings suggest that Lophira lanceolata, particularly its root extract, has therapeutic potential as a complementary intervention for managing snakebite-induced haematological disorders and tissue damage.